(untitled) (Research, Society and Development, 2022)
Cannabis-based products are still not produced in many countries and the great need makes them imported, and often expensive. As an objective, a low-cost extraction method was proposed to facilitate access to the medicinal effects of cannabidiol. The samples of Cannabis sativa used were obtained from in vitro cultivation or from commercially purchased products. Two extraction techniques (ultrasonic extraction and turbo-extraction) and two solvent systems (methanol:chloroform and ethanol) were evaluated. The levels of cannabinoids, total phenolics and total flavonoids were evaluated. The best results were obtained with the turbo-extraction. Ethanol showed a higher yield of cannabinoids, in addition to being a solvent accepted in international conventions in reducing the use of toxic solvents to the environment. Turbo-extraction with ethanol proved to be effective, economical and in line with environmental concerns in the use of ecologically sustainable solvents. As future possibilities, it is proposed to use the information obtained in this study as part of the process of obtaining and subsequent analysis of Cannabis extracts for medicinal purposes.